Effectiveness of Python-based Mathematical Animation in Learning Trigonometric Function - Abdul Jalil Sadana; Haerul Syam; Andi Quraisy (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The abstract nature of trigonometric functions often presents a cognitive barrier for high school students, necessitating visual media capable of representing these concepts with mathematical precision. This study aims to evaluate high school students' perceptions of the effectiveness of Python-based mathematical animations as an interactive learning medium for trigonometric functions. A quantitative descriptive design was employed involving 91 students. The research instrument was a Likert-scale questionnaire measuring four dimensions: understanding, engagement, interest, and motivation. To ensure analytical accuracy, ordinal data were transformed into interval data using a z-distribution weighting procedure (Method of Successive Interval). The findings indicate that the media is highly effective across all dimensions. Specifically, the animation significantly clarified the connection between the unit circle and function graphs (understanding score: 3.5064), maintained high student focus through precise transitions (engagement score: 3.4888), and increased learning enthusiasm (motivation score: 3.4904) by making abstract content more captivating (interest score: 3.2339). The integration of programming-based visualization, with an overall effectiveness score of 3.4299, has proven to enhance students' cognitive and affective experiences. This study provides an empirical basis for using mathematically accurate animations as an innovative instrument to bridge abstraction and improve the quality of trigonometry education at the high school level.